Plans, hopes and ideas for mental health - Ashton, John R. (BJPsych Bull, 2017)
Mental health and the failings of the mental health services are in the spotlight as never before. Nowhere is this more apparent than in the often dire situation with regard to child and adolescent mental health. At the same time, there is a renewed interest in the scope for prevention of mental illness and distress, and in population approaches to mental well-being. It may come as a surprise to some that others have given such serious consideration to strategic approaches to public mental health as long ago as the 1950s. It appears that such consideration was squeezed out by the dominant concerns of serious and enduring mental illness and a prevailing biological view of psychiatry. The time is right to engage with this agenda in recognition of the importance of public mental health, not only for the individual and for families, but also for society as a whole and for the economy. The publication of a review of the subject by the Faculty of Public Health and the Mental Health Foundation is to be commended. Let us make sure it leads to action.